SEARCH FOR NEW PROGNOSTIC OPPORTUNITIES IN MYOCARDITIS - Cherniuk, S.V. (World of Medicine and Biology, 2018)
The aim of the study was to establish predictors of left ventricular systolic dysfunction and to develop the prognostic model for heart failure long-term persistence in patients with acute myocarditis. Material and methods. We performed dynamic observation of 52 patients with acute diffuse myocarditis and reduced left ventricular ejection fraction (LVEF) with II or worse heart failure (HF) functional NYHA class who underwent for immunological study (concentrations of immunoglobuline M, CD16+ and СD19+ lymphocytes, antimyocardial antibody titer, activity of blast-transformation reaction of lymphocytes), echocardiography (LVEF, LV end-diastolic and end-systolic volume indexes) and speckle tracking (longitudinal, circumferential and radial global systolic strain) as also cardiac magnetic resonance imaging. All examinations were performed 3 times: during the 1st month after the disease onset, then after 6 and 12 months of follow-up. Results. The limiting values of the indices determined in the 1st month from the debut of myocarditis have been obtained, which can serve as predictors for the presence of a reduced LV EF after 6 months: immunoglobulin M > 2.5 g/l, CD16+ > 0,32 × 109/l, titer of antibodies to the myocardium > 20.0 conv. units, and activity of blast-transformation reaction of lymphocytes > 5.9%. A mathematical model has been developed that can predict persistence of heart failure functional class at the level of II or higher after 12 months or improvement in the clinical course of myocarditis with the presence of class I or absence of HF. Sensitivity of the model is 86,2%, specificity - 83,2%, positive prognostic value - 83,2%, negative prognostic value - 72,3%. Conclusions. We established predictors of LV systolic dysfunction and developed the mathematical model for predicting heart failure in patients with acute diffuse myocarditis.
Keywords: left ventricular systolic dysfunction; speckle tracking echocardiography; acute diffuse myocarditis; predictors of systolic dysfunction